Light‐Regulated Stapled Peptides to Inhibit Protein–Protein Interactions Involved in Clathrin‐Mediated Endocytosis1. Issue 30 (17th June 2013) - Nevola, Laura; Martín‐Quirós, Andrés; Eckelt, Kay; Camarero, Núria; Tosi, Sébastien; Llobet, Artur; Giralt, Ernest; Gorostiza, Pau
<x xml:space="preserve">Abstract</x> Control of membrane traffic: Photoswitchable inhibitors of protein–protein interactions were applied to photoregulate clathrin‐mediated endocytosis (CME) in living cells. Traffic light (TL) peptides acting as "stop" and "go" signals for membrane traffic can be used to dissect the role of CME in receptor internalization and in cell growth, division, and differentiation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>